Nos organizamos para establecer nuestras normas de convivencia - Rodríguez Castro, Yngrid Lizbeth (2020)
We organized the present put a title to session to establish our standards of get-together, it corresponds to social staff's area of area, taking the competition into account he lives together and participate democratically in the search of the public interest, capacity interacts with everybody, the coparty got his performance activities with their companions obeying their differences and treating them with kindness and respect. Fulfill their duties at the classroom for benefit of all and according to his age. In order to count on a healthy climate we should learn how to live together, within a society, taking democratically part in the solution of problems, looking for the public interest of all. In the development of this session motivating and challenging activities that the achievement of competitions, capacities and performances promote were applied. He had in account the pedagogic processes like motivation problematization, learning's construction of learning and information processing, application, transference and evaluation, besides the didactic processes of social staff's area problematization informational analysis, photo of decisions. The active participation of the students of individual and group way was promoted. The used strategies were chords with the students' age those who are immersed to the activities of the game and their rules.